Nrf2 Activation With CDDO-Methyl Promotes Beneficial and Deleterious Clinical Effects in Transgenic Mice With Sickle Cell Anemia - Ihunnah, Chibueze A.; Ghosh, Samit; Hahn, Scott; Straub, Adam C.; Ofori-Acquah, Solomon F. (Frontiers in Pharmacology, 2022)
Activation of Nrf2, a major transcription factor that drives the antioxidant defense system, is an emerging therapeutic strategy in Sickle Cell Disease (SCD). In this study, transgenic Sickle Cell Anemia mice (SS mice) treated with CDDO-Methyl (CDDO-Me), a potent Nrf2 activator, showed reduced progression of hemolytic anemia with aging, but surprisingly also showed reduced endothelial function. Pulmonary vessels isolated from SS mice treated for four months with CDDO-Me displayed a diminished response to nitric oxide (NO)-induced vasodilation compared to littermates given vehicle. It is unclear what molecular mechanism underly the vascular impairment, however, our in vitro assays revealed that CDDO-Me induced the expression of the endothelin receptor (ETA and ETB ) in vascular smooth muscle cells. Endothelin signaling is associated with increased vascular tone and vasoconstriction. This study underscores the importance of pre-clinical benefit-risk investigations of Nrf2 activating compounds which may be used to treat patients with SCD.